Comparative study of on-the-job training models for Chinese and American coaches - Liu, P.; Yang, H. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Providing on-the-job training for coaches is a benefit to the coach as well as the sustainable development of competitive sports. China and America approach on the-the-job training for coaches differently due to different political and economic systems, as well as cultural background. Professionals in the Chinese sports community commonly attempt to find ways to incorporate the traits of America which is a powerful country that reinforces an international exchange and connection in on-the-job training for their coaches. For this purpose, the researchers attempted to compare and analyse the characteristics of on-the-job training models for both Chinese and American coaches to find the commonalities and differences, to incorporate strong practices and remove weaker ones, and to help improve on-the-job training for Chinese coaches. Methods The researchers compared the characteristics of the on-the-job training models for Chinese and American coaches through a review of the literature and logical analysis. Results The on-the-job training methods for both Chinese and American coaches are very similar including the scientific theory, technique, and practice. The training of the American coaches places importance on the teaching material and curriculum. The training of the Chinese coaches strives to combine training and practice and stresses practical training. Both China and America include grading in their models, however, America places importance on graduation. Both countries place importance on integrating theory and practice and China is not as strong in putting process into practice. The institutions in both China and America set up strict on-the-job training organizations and take the training of coaches seriously, including the grading system, training, assessment, continuous education, and the management of the system. The top institutions have a plan, incorporating feedback and complete implementation. On-the-job training in America has funding support, while that in China does not have enough funding. The majority of Chinese coaches are retired athletes, while those in America begin their training in high school. Conclusions The American model of developing their coaches is a good reference for coaches` on-the-job training in China. In the future, on-the-job training in China should pay attention to combining theory and practice, transforming the knowledge to ability, and improving the quality of coaches in China. Meanwhile, it is necessary to ensure the development of employment opportunities in providing on-the-job training for coaches. It is suggested that the General Administration of Sport invest more money in holding seminars, purchasing teaching materials, appraising the system, and devloping information.